Pengukuran Kinerja pada Departemen Produksi Amonia 1B PT. Petrokimia Gresik Berbasis Metode Balanced Scorecard - Fajarillah, Agung; Andesta, Deny (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the performance of the Ammonia Plant of PT Petrokimia Gresik using the Balanced Scorecard method to provide an alternative performance measurement system that can provide an understanding to management about the company's performance appropriately and thoroughly. The Balanced Scorecard method is one of the performance measurement methods that reviews company performance not only from the Financial side, but also Non-Financial. The performance index of the PT Petrokimia Gresik Ammonia Plant in 2020 is 1,891 and in 2021 it is 1,892, this means that overall the PT Petrokimia Gresik Ammonia Plant has decreased by 0.001.